Long-term starvation effects on Mus musculus hepatocyte nuclear phenotypes - Mateus, R. P. [UNESP]; Taboga, S. R. [UNESP] (Firenze University Press, 2001)
Starvation is a physiologic stress and can significantly alter the structure of hepatic cells. This work aims to detect morphological changes in mice hepatocyte under starvation physiologic stress, based on silver staining technique. Fourteen 21 day old male mice (Mus musculus) were used, 5 as control, 5 submitted to 72 hours of starvation, and 4 were refed during 72 hours after 72 hours of starvation. After liver imprint, 15 nuclei per mouse and their respective nucleoli were outlined in millimetric paper and their areas were obtained. The results, in mm2, were transformed into μm2. The number of nucleoli per nuclei were also counted. After starvation, a statistically significant rise in nuclear and nucleolar areas occurred and no significant increase in the number of nucleoli was observed. The refeeding caused a partial recovery of the nuclear area, no significant change in the nucleolar area and a statistically significant increase in the number of nucleoli. Therefore, starvation can be considered as a modifier agent of the chromatinic structure, leading to an increase of the nuclear and nucleolar areas probably due to an increment of RNA and protein synthesis. The recovery of the stress (refeeding) did not presented a decrease of nucleolar area and evidenced a nucleoli fragmentation, probably to increase more the protein synthesis and/or due to its cycle during the interphase.
Keywords: AgNOR; Hepatocytes morphology; Nuclear and nucleolar morphometry; Nucleolus; Refeeding; Starvation